2006
DOI: 10.1038/sj.ki.5000418
|View full text |Cite
|
Sign up to set email alerts
|

BOLD-MRI for the assessment of renal oxygenation in humans: Acute effect of nephrotoxic xenobiotics

Abstract: Hypoxia of renal medulla is a key factor implicated in the development of drug-induced renal failure. Drugs are known to influence renal hemodynamics and, subsequently, affect renal tissue oxygenation. Changes in renal oxygenation can be assessed non-invasively in humans using blood oxygenation level-dependent magnetic resonance imaging (BOLD-MRI). This study was designed to test the acute effects of administration of specific drugs in healthy human kidney oxygenation using BOLD-MRI. Acute changes in renal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 30 publications
6
84
1
3
Order By: Relevance
“…Such approaches offer significant advantages in detecting pathological changes that may be regional or heterogeneous in their effects, and are forming the basis of our future studies. Renal T 2 * and BOLD contrast Although we could confirm the previously reported differences between the R 2 * of the cortex and medulla [17,19], we observed no change in renal R 2 * on physiological perturbation [21,34,35] as previously ascribed to changes in tissue oxygenation via BOLD contrast mechanisms [36]. Some earlier studies have employed hand-placed regions of interest to assess changes in R 2 * , typically using T 2 * or R 2 * maps to guide selection of ROI position.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Such approaches offer significant advantages in detecting pathological changes that may be regional or heterogeneous in their effects, and are forming the basis of our future studies. Renal T 2 * and BOLD contrast Although we could confirm the previously reported differences between the R 2 * of the cortex and medulla [17,19], we observed no change in renal R 2 * on physiological perturbation [21,34,35] as previously ascribed to changes in tissue oxygenation via BOLD contrast mechanisms [36]. Some earlier studies have employed hand-placed regions of interest to assess changes in R 2 * , typically using T 2 * or R 2 * maps to guide selection of ROI position.…”
Section: Discussionsupporting
confidence: 82%
“…These methods have been translated from brain imaging studies that employ changes in tissue R 2 * to report on neural activity via blood oxygenation [13]. Applied to renal tissue, studies have suggested that changes in cortical and medullary oxygenation can be monitored via R 2 * mapping, and that tissue oxygenation change in response to physiological perturbations (including water loading) can differ between normal and disease states [14][15][16][17][18][19], including type 2 diabetes [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Radiocontrast administration induces a host of systemic effects that may compromise renal tissue oxygenation, including pulmonary ventilation-perfusion mismatch, reduced cardiac output and renal perfusion pressure, altered rheologic properties of the blood, and increased oxygen-hemoglobin association (12). However, the greater part of the decline in renal parenchymal oxygenation can be attributed to altered intrarenal balance of oxygen supply and demand, summarized in Figure 2 and as discussed in the sections that follow.…”
Section: Physiologic Medullary Hypoxia Aggravated By Radiocontrast Amentioning
confidence: 99%
“…12,22,42,[55][56][57][58][59] In rats treated with cyclooxygenase and nitric oxide synthase inhibitors, administration of a first-generation ionic hyperosmolar contrast agent reduced medullary oxygenation. 55 Administration of a third-generation nonionic, iso-osmolar, high viscosity contrast agent caused an even greater reduction in medullary oxygenation.…”
Section: Contrast-associated Nephropathymentioning
confidence: 99%